Adaptative techniques for the human faces detection - Marar, João Fernando [UNESP]; Costa, Danilo Nogueira [UNESP]; Pinheiro, Olympic Jose [UNESP]; Costa de Barros Carvalho Filho, Edson (My University, 2004)
This paper presents results from an efficient approach to an automatic detection and extraction of human faces from images with any color, texture or objects in background, that consist in find isosceles triangles formed by the eyes and mouth.
Keywords: Artificial Neural Network; Backpropagation; Face Recognition; Feature Extraction; Machine Vision and Image Processing; Adaptive Architecture; Adaptive architecture; Automatic detection; Machine vision and image processing; Computer architecture; Computer vision; Feature extraction; Image processing; Neural networks; Face recognition